Men's perceptions of living with osteoporosis: a systematic review of qualitative studies. (May 2019) - Compton, Marie; Ben Mortenson, W.; Sale, Joanna; Crossman, Alex; Ashe, Maureen C.
Abstract: Background: One in five men will experience an osteoporosis-related fracture in their lifetime. However, osteoporosis is widely perceived as a women's disease and few studies focus specifically on men. Our objective was to identify qualitative evidence to understand men's perceptions of osteoporosis and fracture. Methods: We conducted a systematic review following standardized guidelines. We identified qualitative studies that included men aged 18 years and over using the terms: osteoporosis, fragility or low-trauma fracture, bone health; and perceptions or experiences with osteoporosis and fractures. We appraised the quality of data and used a meta-aggregative approach to synthesize findings. Results: We identified four publications, based on three studies (n = 61 participants); one of the publications was a secondary analysis. The following themes were developed from the literature: (1) perceived healthcare gap for men; (2) strong focus on women, with a need for support from spouses and health professionals; and (3) three general responses to men's osteoporosis self-management: limiting lifestyle, minimizing importance of diagnosis, and risk taking. Conclusions: The most striking finding from this review was the lack of available qualitative evidence. However, it emerged that the present focus of osteoporosis as a women's disease may influence how men develop self-management strategies. These data highlight the need to include men in future osteoporosis health-related conversations and interventions. Systematic review registration: CRD42018093999.